2021
DOI: 10.3390/ijerph182312736
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Contribution of Proximal Family Risk Factors on SLC6A4 DNA Methylation in Children with a History of Maltreatment: A Preliminary Study

Abstract: The cumulative effects of proximal family risk factors have been associated with a high number of adverse outcomes in childhood maltreatment, and DNA methylation of the serotonin transporter gene (SLC6A4) has been associated with child maltreatment. However, the relationships between proximal family risk factors and SLC6A4 methylation remains unexplored. We examined the association among cumulative family risk factors, maltreatment experiences and DNA methylation in the SLC6A4 gene in a sample of 33 child vict… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Other included studies focused on contextual, family and psychopathological issues to assess the risk and impact of domestic violence on children and adolescents (Craig et al 2021;Diamond and Muller 2004;Erolin et al 2014;Flander et al 2009;Sičić and Mužinić 2007;Sidebotham and Heron 2006;Vial et al 2020a). These studies found that the presence of psychiatric problems prior to pregnancy, a low parental age, low academic performance, the socioeconomic environment of families and the prematurity of children can all determine behaviors that influence parenting patterns, increasing the risk of mistreatment (Sidebotham and Heron 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other included studies focused on contextual, family and psychopathological issues to assess the risk and impact of domestic violence on children and adolescents (Craig et al 2021;Diamond and Muller 2004;Erolin et al 2014;Flander et al 2009;Sičić and Mužinić 2007;Sidebotham and Heron 2006;Vial et al 2020a). These studies found that the presence of psychiatric problems prior to pregnancy, a low parental age, low academic performance, the socioeconomic environment of families and the prematurity of children can all determine behaviors that influence parenting patterns, increasing the risk of mistreatment (Sidebotham and Heron 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of the study by Craig et al (2021) was to examine the extent to which the cumulative family risk and number of maltreatment experiences affect DNA patterns, specifically the SLC6A4 gene. In more than 90% of children who suffered more than one type of maltreatment in childhood, the index of cumulative exposure to family risk factors revealed a significant positive association with DNA mutation patterns in two different genes (SLC6A4 and CpGs).…”
Section: Cumulative Familial Risk and Change In Genetic Pattern In Ch...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are also consistent with the added value of using measures of maltreatment that span a wider range of severity and types of exposure [ 13 ]. Nevertheless, the putative effects of child maltreatment on DNAm should also be considered along other family risk factors (e.g., maternal and/or paternal psychopathology, alcohol and/or drug abuse), as preliminary evidence suggests that these additional stressful family experiences may have a cumulative effect on DNAm levels above and beyond child maltreatment (e.g., [ 73 ]). Moreover, the role of DNAm could be conditional on the allelic variations within the selected candidate genes (e.g., [ 74 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Human studies have also investigated the association between epigenetic modifications of the SLC6A4 gene and sexual aggression. Research conducted on individuals with a history of early-life trauma or exposure to adverse experiences has revealed differences in DNA methylation patterns in the SLC6A4 gene [ 132 ]. These Epigenetic modifications of the SLC6A4 gene can affect serotonin reuptake, leading to imbalances in serotonin availability and compromised neurotransmission, which may contribute to the manifestation of sexual aggression [ 133 , 134 ].…”
Section: Introductionmentioning
confidence: 99%